Begonia fenshuilingensis, a new species in Begonia sect. Platycentrum (Begoniaceae) from southeastern Yunnan, China - Feng, Xin-Xin; Liu, Zhi-Xian; Wei, Dan; Li, Ren-Kun; Huang, Yu-Ni; Guo, Le-Dong; Guo, Wei; Chen, Su-Fang (Phytotaxa, 2021)
Begonia fenshuilingensis X.X.Feng, R.K.Li & Z.X.Liu, a new species in Begonia sect. Platycentrum (Klotzsch) A.DC. (Begoniaceae) from southeastern Yunnan, China, is here described and illustrated. It morphologically resembles B. dryadis and B. daweishanensis, but differs by its fleshy trigonous-ellipsoid capsules without wings. Molecular phylogenetic analysis of ITS sequence data supports the new species as monophyletic, and distinct from the two similar species. Due to its limited distribution, we consider the new taxon as “Vulnerable D2” (VU D2) according to the IUCN Red List Categories and Criteria.